1992
DOI: 10.1088/0953-2048/5/8/001
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen diffusion in c-axis-oriented YBa2Cu3Oxfilms

Abstract: C-axis-oriented YBa,Cu,O,., films produced by electron beam and thermal evaporation are composed of mosaic blocks. The deoxygenated YBa,Cu,O, (x = 6 . 1 4 2 ) films were annealed in an oxygen atmosphere. The change of oxygen concentration in t h e films during t h e annealing process was detected by the diffraction peak site of the (00 il) peak. Applying t h e theory of lattice diffusion to analyse the oxygen indiffusion in the'films. w e obtain the activation energiesfoi oxygendiffusioninthetetragonalandortho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

1993
1993
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 7 publications
2
10
0
Order By: Relevance
“…This idea has been realized in many groups by substituting fluorine-free salt(s) for one or two specific TFA salt(s) in the precursor solution. To the best of our knowledge, there were mainly three routes of metal salt substitution(s): (1) Cu salt [7]; (2) Cu and Y salts [8,9]; (3) Cu and Ba salts [10]. Relative to the conventional TFA-MOD solution (100% fluorine content), the fluorine contents in these precursor solutions could be estimated to be about 53.8%, 30.8% (or 23.1% if the poor-Ba stoichiometry is used [11]) and 23.1%, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…This idea has been realized in many groups by substituting fluorine-free salt(s) for one or two specific TFA salt(s) in the precursor solution. To the best of our knowledge, there were mainly three routes of metal salt substitution(s): (1) Cu salt [7]; (2) Cu and Y salts [8,9]; (3) Cu and Ba salts [10]. Relative to the conventional TFA-MOD solution (100% fluorine content), the fluorine contents in these precursor solutions could be estimated to be about 53.8%, 30.8% (or 23.1% if the poor-Ba stoichiometry is used [11]) and 23.1%, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…We can classify these data according to the following four groups: powders [5,8,11], polycrystalline ceramics [7-9, 14, 16, 23], thin films [4,6,13,15,17,21,35,36] and single crystals [2,3,22].…”
Section: Resultsmentioning
confidence: 99%
“…However, because of an imperfect crystal structure (due to microcracks, twin and low-angle grain boundaries, acting as 'chimneys' in the c-direction) L can be much smaller than the lateral sample size [34][35][36]. Since L depends sensitively on the microstructure of the sample, it may vary considerably between different samples and may be the main source for the large variations of the oxygen diffusion coefficient reported in the literature.…”
Section: Theoretical Aspectsmentioning
confidence: 99%
“…The bulk diffusion of oxygen in YBCO 6ϩx is highly anisotropic and takes place predominately in the ab plane, especially at temperatures below 670 K. 30 However, c-axis-oriented YBCO 6ϩx films consist of various grains whose mosaic boundaries act as short circuits for oxygen diffusion. 31,32 Typical activation energies for bulk and interface diffusion of oxygen in YBCO 6ϩx are about 1 eV. [33][34][35] It was observed that activation energies for oxygen out-diffusion are higher than those for oxygen in-diffusion.…”
Section: ͑6͒mentioning
confidence: 99%